Fire Resistance in American Heavy Timber Construction History and Preservation - Heitz, Jesse; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume presents a history of heavy timber construction (HTC) in the United States, chronicling nearly two centuries of building history, from inception to a detailed evaluation of one of the best surviving examples of the type, with an emphasis on fire resistance. The book does not limit itself in scope to serving only as a common history. Rather, it provides critical analysis of HTC in terms of construction methods, design, technical specifications, and historical performance under fire conditions. As such, this book provides readers with a truly comprehensive understanding and exploration of heavy timber construction in the United States and its performance under fire conditions.
Chapter 1 American Heavy Timber Construction -- Chapter 2 The Origins of Heavy Timber Construction -- Chapter 3 The Great Chicago Fire and Heavy Timber Construction -- Chapter 4 Heavy Timber in the Midwest -- Chapter 5 The End of Heavy Timber Construction -- Chapter 6 The Performance of Heavy Timber Construction -- Chapter 7 The Resurgence of Heavy Timber Construction -- Chapter 8 A Hope for Survival -- Chapter 9 Conclusion.
Keywords: Building materials; Buildings -- Design and construction; Light construction; Steel construction; Lightweight construction; Biogeography; Building Materials; Building Construction and Design; Light-weight Construction, Steel and Timber Construction; Structural Materials; Biogeosciences